2020
DOI: 10.3390/ijms21165629
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Specific Molecular Test for Mutations in the Diagnosis of Thyroid Nodules: A Prospective Study of BRAF-Prevalent Population

Abstract: Molecular testing offers more objective information in the diagnosis and personalized decision making for thyroid nodules. In Korea, as the BRAF V600E mutation is detected in 70–80% of thyroid cancer specimens, its testing in fine-needle aspiration (FNA) cytology specimens alone has been used for the differential diagnosis of thyroid nodules until now. Thus, we aimed to develop a mutation panel to detect not only BRAF V600E, but also other common genetic alterations in thyroid cancer and to evaluate the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…As previously reported by Song et al [31] found that the PAX8/PPARG gene mutation rate in Asians was much lower than in westerners. Consistently, PAX8/PPARG gene mutations were not reported in the multi-gene study by Yoon Young Cho et al [14]…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As previously reported by Song et al [31] found that the PAX8/PPARG gene mutation rate in Asians was much lower than in westerners. Consistently, PAX8/PPARG gene mutations were not reported in the multi-gene study by Yoon Young Cho et al [14]…”
Section: Discussionsupporting
confidence: 64%
“…It is worth noting that different races may vary in molecular alterations in this type of tumor. Previous research showed that the common mutated gene: BRAF V600E , ranged from 29% to 83% (mean: 45%) in papillary thyroid cancer (PTC), [11,12] with higher alternation frequency in Asian people (70-80%) [13,14] and lower mutations in the Americans (40-50%), [15] although the rate has increased in the recent decade. [16] Given the growing need for individualized diagnosis and therapy, neither mere cytology nor single-gene testing is satisfactory for clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FVPTC was the dominant pathology (61%) in malignancies, and the positive rate of BRAF V600E mutation was low (4% of all tumors) because thyroid nodules with AUS/FLUS cytology were investigated. In the literature, RAS is the most prevalent mutation and FVPTC, rather than classic PTC, is the most common malignancy in nodules with indeterminate cytology ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…PTC is usually characterized by chromosomal rearrangements of RET or point mutations in the RAS or BRAF proto-oncogene, and mutations in the BRAF, RAS, or RET genes are found in nearly 70% of PTC cases [19,29]. Of these, BRAF mutations are seen in 60%-70% of PTCs, making them the most common mutations in PTC [30,31]. Yan et al showed that 1715 of 2048 patients with PTC had BRAF V600E mutations, with a mutation rate of 83.7% [32].…”
Section: Discussionmentioning
confidence: 99%